2014
DOI: 10.1063/1.4902514
|View full text |Cite
|
Sign up to set email alerts
|

Influence of O2 on the dielectric properties of CO2 at the elevated temperatures

Abstract: SF 6 gas is widely used in the high voltage circuit breakers but considering its high global warming potential other substitutes are being sought. Among them CO 2 was investigated and even has been used in some practical products. However, at room temperature, the dielectric properties of CO 2 are relatively lower than SF 6 and air. The goal of this work is to investigate a CO 2 -based gas to improve the performance of the pure CO 2 . In this paper, the dielectric properties of hot CO 2 /O 2 mixtures related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 55 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…The influence of O 2 on the dielectric properties of CO 2 at the elevated temperatures in discharge explored by Rong et al [41] also indicates that CO 2 –O 2 mixtures have a much better dielectric strength than both the pure CO 2 and air. It was pointed out that the electron energy distribution function increase with O 2 content due to the vibrational cross‐sections of O 2 is smaller than that of CO 2 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The influence of O 2 on the dielectric properties of CO 2 at the elevated temperatures in discharge explored by Rong et al [41] also indicates that CO 2 –O 2 mixtures have a much better dielectric strength than both the pure CO 2 and air. It was pointed out that the electron energy distribution function increase with O 2 content due to the vibrational cross‐sections of O 2 is smaller than that of CO 2 .…”
Section: Resultsmentioning
confidence: 98%
“…In addition, the increase of η/N is attributed to the strong electronegativity of O 2 . Furthermore, the attachment cross-section of O 2 is larger than CO 2 for electron energy around 5-10 eV, which could lead to a reduction of the electron kinetic energy [40] The influence of O 2 on the dielectric properties of CO 2 at the elevated temperatures in discharge explored by Rong et al [41] also indicates that CO 2 -O 2 mixtures have a much better dielectric strength than both the pure CO 2 and air. It was pointed out that the electron energy distribution function increase with O 2 content due to the vibrational cross-sections of O 2 is smaller than that of CO 2 .…”
Section: Influence Mechanism Of O 2 On Insulation Properties Of C 4 Fmentioning
confidence: 99%
“…Alternative arc-extinguishing gases for gas circuit breakers are roughly categorized into two types, natural gases such as CO 2 , N 2 , O 2 , and so on, and artificial gases such as C 5 F 10 O, CF 3 I, C 4 F 7 N, and so on. As specifically proposed examples, CO 2 and its combinations, such as CO 2 /O 2 , CO 2 /C 5 F 10 O, CO 2 /CF 3 I, CO 2 /O 2 /C 4 F 7 N, and CO 2 /O 2 /C 5 F 10 O, have been researched [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Here, the artificial gases should be mixed with natural gases, and not be used alone, because of their high liquefying temperature.…”
Section: Introductionmentioning
confidence: 99%
“…were calculated at condition that reduced ionization coefficient (α/N) and reduced attachment coefficient (η/N) are in equilibrium, therefore the effective ionization coefficient equal to zero ( = (α/N)-(η/N) =0), this method was used by (Láska et al, 1984;Brand and Kopainsky, 1979;Itoh et al, 1980; to calculate electrical breakdown voltage using two-term approximation solution of Boltzmann equation. Critical field strength have been studied by both theoretical calculations (Tanaka, 2004;Rong et al, 2014;Zhao and Lin, 2016; and experimentally to find new gases with high dielectric field strength which used in electrical insulator, for example, experimentally (Xiao et al, 2018) reported that small addition of oxygen O 2 reduced breakdown voltage of the c-C 4 F 8 /N 2 mixed gas. (Beaty, et al 1979 andDutton, 1975) published a large data on the electron swarm parameters in number gases over a wide range of electric field strength E/N.…”
Section: Introductionmentioning
confidence: 99%